Relationship between teachers' motivational strategies, self-efficacy and beliefs on students' academic achievement at Oman public schools - Al-Rawahi, Talal Salim Sangoor; Che Hassan, Norlizah; Ismail, Asmah (Human Resource Management Academic Research Society, 2019)
The aims of the study is to determine the relationship between teachers’ motivational strategies, self-efficacy, general beliefs and students’ academic achievements. The study sample comprised of 135 teachers from eight secondary public schools in Oman. Drawing on the findings from a correlational survey design study, the paper identified that there were high level of teachers’ motivational strategies, high level of teachers’ self-efficacy, high level of teachers’ general beliefs and moderate level of students’ academic achievements. In addition, there is a positive significant relationship between teachers’ self-efficacy and students’ academic achievements and a positive significant relationship between teachers’ general beliefs and students’ academic achievements. However, there was no significant relationship between teachers' transient beliefs and students’ academic achievements. When teachers adopt the view of students’ motivation as stable and malleable, and adopt a helplessness response, it negatively predicts a supportive environment and better academic achievements. This is undoubtedly the most difficult attitude of the teachers to change, but it holds perhaps the most potential for dramatic improvement in students’ motivation. The findings of this study may serve as a platform for school authorities, administrators and policymakers to develop teachers’ motivational strategies that can be practised in Oman public schools.